Comparative analysis of the table tennis plastic ball and celluloid ball in terms of racket angle - Ferrer, N. P.; Santelices, O. Y.; Maghanoy, M. N.; Wisdom Valleser, C. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
On July 1, 2014, the ITTF started implementing the use of the plastic ball in all ITTF sanctioned and World Title events, instead of the traditional celluloid ball. In addition to the material change from celluloid to plastic, there was also a slight change in the diameter and the weight of the ball from 39.50mm-40.50mm to 40.00mm-40.60 mm and from 2.67g-2.77g to 2.65g-2.82g. The change in material, together with the change in diameter and weight, can greatly affect the game of table tennis and how it is viewed and played. Since this is a new and recent change and development in the sport, there are still a lot of areas to be looked into and studied. The purpose of this study was to determine if there is a significant difference between the racket angles among the Philippine Men`s Table Tennis National Team Players when using the plastic ball compared with that when using the celluloid ball. A quantitative, experimental, and within subject research design was used in this study. All 3 subjects were tested for both the plastic ball and the celluloid ball and repeated racket angle measurements were taken for all participants. Results showed that among the group, there was a statistically significant difference between the racket angle measurements for the celluloid ball and plastic ball. Significant differences were also found in each one of the three player`s racket angle measurements for the celluloid ball when compared to each one`s own individual racket angle measurements for the plastic ball.